Bio‐Orthogonal Chemistry in Cell Engineering. Issue 3 (21st December 2022) - Wang, Yixin; Hu, Quanyin
Abstract : Cell therapy holds great promise in addressing a wide range of malignant diseases, such as cancers and infectious diseases. The convergence of chemistry, engineering, and material sciences further create tremendous opportunities to upgrade their therapeutic potential by integrating them with different functional motifs, which can strengthen the inherent features of cells and further render them with new functionalities. A rational selection of the cell decoration methods is of great importance to ensure desired cell modification while maximumly preserving the properties and biofunctions of cells. Bio‐orthogonal chemistry allows covalent modification of cells at favorable reaction rates under mild biological conditions without the perturbation of the biofunctions of the engineered cells or disturbance of the biosystem. Among various types of bio‐orthogonal reactions, cycloaddition reactions are widely adopted for cell engineering. This review presents a summary of the latest progress in the development of bio‐orthogonal chemistry‐based strategies for cell engineering with a focus on cycloaddition reactions, highlights their applications in disease diagnosis and therapy, and discusses the prospects of this cell engineering technique. Abstract : The development of cell therapy has benefited immensely from various engineering techniques. Bio‐orthogonal chemistry represents a facile and useful tool to modify cells without the perturbation of their functions. This review introduces the strategies to functionalize cells via bio‐orthogonal chemistry and highlights their applications in disease diagnosis and therapy.